الأفاق المستقبلية للمعلوماتية وأثرها على المجتمع - الدكتور هلال عبود البياتي (PROSPECTIVE RESEARCHES, 2023)
At the end of 20th century, we have witnessed a new era of information technology called informatics which involves information processing with retrieval and documentation of information and knowledge inference using computer hardware and software and their complicated economical, political and social effects on the individual and society. Information will eventually effects the international relationships among different societies and countries cross the boarders. The Arabs need to consider seriously all the steps needed at the strategic and planning levels executing foreign solutions and to present national strategies. They are also required to take preplanning step of informatics and to expand the use of Arabic researches and computer programming. In addition, the Arabs are required to utilize informatics that is available in the Islamic Arab heritage through using modern information techniques to open new vistas among nations on one hand, and to keep our heritage, language and religion from any negative effects on the other.